WANITA DALAM PENDIDIKAN ISLAM KLASIK - Sihaloho, Wardani (UIN Sumatera Utara Medan, 2023)
In Islam, women are required to seek knowledge just like men. Islam has equated women and men in matters of spirituality and religious obligations without any differences in the fields of knowledge and education. The Messenger of Allah SAW said which means: